2019
DOI: 10.1111/ajt.15204
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of the DeKAF cross-sectional cohort study

Abstract: The DeKAF study was developed to better understand the causes of late allograft loss. Preliminary findings from the DeKAF cross‐sectional cohort (with follow‐up < 20 months) have been published. Herein, we present long‐term outcomes in those recipients (mean follow‐up ± SD, 6.6 ± 0.7 years). Eligibility included being transplanted prior to October 1, 2005; serum creatinine ≤ 2.0 mg/dL on January 1, 2006; and subsequently developing new‐onset graft dysfunction leading to a biopsy. Mean time from transplant to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Primary humoral alloimmune activation through dnDSA production is a well-characterized deleterious factor inducing chronic ABMR and accelerated graft loss ( 1 , 2 ) and recent reports have recently shown that it may be predicted by quantifying the donor/recipient HLA MM at the molecular level ( 6 , 31 ). However, for B-cell activation in absence of preformed immune memory, cognate T-cell help is required thus, previous de novo T-cell alloimmune priming (dnDST) against donor antigens might also occur, subsequently driving anti-donor humoral immune activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary humoral alloimmune activation through dnDSA production is a well-characterized deleterious factor inducing chronic ABMR and accelerated graft loss ( 1 , 2 ) and recent reports have recently shown that it may be predicted by quantifying the donor/recipient HLA MM at the molecular level ( 6 , 31 ). However, for B-cell activation in absence of preformed immune memory, cognate T-cell help is required thus, previous de novo T-cell alloimmune priming (dnDST) against donor antigens might also occur, subsequently driving anti-donor humoral immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting survival of kidney transplantation is greatly challenged by both preformed and primary donor-specific humoral alloimmunity: the former preventing access to transplantation in sensitized patients, and the latter accelerating chronic rejection and premature graft loss ( 1 , 2 ). Between 5 and 9% of kidney transplant recipients may develop de novo donor-specific antibodies (dnDSA) each year mainly against class-II human leukocyte antigens (HLA) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histologic analysis of the "index biopsy" has been described in detail. [13][14][15][16] Representative histologic sections were submitted to a central laboratory for analysis; biopsy specimens were interpreted without knowledge of the clinical diagnoses or C4d positivity, by the same pathologist (JG), using the Banff' 97 classification. 2 Scoring of peritubular capillary infiltrates was done as per the Banff 2005 classification.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…(3) i-IFTA continued to be associated with DC-GS after adjusting for Banff "i" score, 13,14 serum creatinine at the time of biopsy, interstitial fibrosis (ci), tubular atrophy (ct), C4d staining, and the presence of donor specific antibody (DSA). In this report, we analyze the impact of i-IFTA and t-IFTA on outcomes in the DeKAF prospective cohort, a much larger population than the C-S cohort and with outcomes available from the time of transplant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the decision to biopsy is usually based on noninvasive estimates of allograft function that lack sensitivity, 6 and often detect established phenotypes of late acute rejection that are difficult to treat and hasten allograft failure. 7 , 8 …”
mentioning
confidence: 99%